GENETIC FOUNDATION OF BROWN ADIPOSE TISSUE AND ITS ROLE IN CHILDHOOD OBESITY - Maksimovic, Nela; Perovic, Dijana; Perovic, Vladimir; Dusanovic Pjevic, Marija; Grk, Milka (Medical Research, 2025)
Obesity is a chronic complex disease, defined by excessive fat deposits, that may have adverse health consequences. Long-term childhood obesity has been linked to the development of different chronic illnesses and is often accompanied by various psychological and social issues. It typically develops due to complex, subtle biological predispositions, exacerbated by social and environmental factors that promote obesogenic behaviors. Brown adipose tissue (BAT) was initially identified as a thermogenic organ in small rodents and human infants. Although its amount decreases with age, adults retain some metabolically active functional BAT tissue, which can help regulate metabolism and energy expenditure, making it a potential target for obesity treatments. Metabolic stress can lead to the "whitening" of BAT, associated with its dysfunction and the development of inflammation and systemic metabolic disorders. Conversely, the transformation of white adipose tissue (WAT) into thermogenic BAT, a process known as "browning", represents another form of adipose tissue “transdifferentiation". In this complex network, specific genes, such as UCP1, PRDM16, PPARG, PPARGC1A, and EBF2, were identified. Identification of polymorphic variants within BAT-related genes, as well as the hormonal regulation, neurotransmission, and inflammation associated with BAT, could enhance our understanding of the causes of obesity and facilitate the development of novel treatments. This review summarizes recent studies on the genetic regulation of brown adipose tissue (BAT) differentiation and transdifferentiation, as well as gene variants that may predispose individuals to obesity at an early age. Based on this genetic foundation, we also explore and summarize mechanisms to prevent the "whitening" of BAT and its functional decline.